IMPLEMENTASI STANDAR PENGELOLAAN PENDIDIKAN DI SMAN 1 TUALANG KABUPATEN SIAK - LINATUL MULAIKAH; RR. SRI KARTIKOWATI; SUMARNO SUMARNO (Universitas Riau, 2017)
This study aims to gain a deep Understendingof the process of Implementationof national education ministerial decree number is of 2007 on education manajement standarImplemented in SMAN 1 Tualang kabupten Siak. This study used a qualitative approach withcase study method. In thisstudy purposively selected sample. Data collection is done byobservation,interview, and documentation. Data analisys is done trough a process of data reductiondata display and drawing conclusion/verification. Data validity checking the validity could betested through the form trianggulationand member checking. The results of this study wastoreveal three findings: 1) School work plan in achieping educational management standars 2)The Implementation of the work plan management scholl in a cheving education standars, 3)Monitoring and evaluation in achieving standars of management education, monitoring andevaluation in achiving standars of management education. The result showed that theimplementation Permendiknas No. 19, 2007 years. This due to the understanding of the manageras well as the seriosness of the parties involved in managing educational management standarin SMAN 1 Tualang Kabupaten Siak.